2002
DOI: 10.1097/00002030-200208160-00012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the cause of death among HIV positive subjects across Europe: results from the EuroSIDA study

Abstract: The proportion of pre-AIDS deaths increased from 1994 to 2001; however, the incidence of pre-AIDS deaths and deaths overall declined. IDU and subjects from northern/eastern Europe had an increased risk of pre-AIDS death. HIV-positive patients live longer therefore it is essential to continue to monitor all causes of mortality to identify changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
181
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(197 citation statements)
references
References 28 publications
12
181
0
4
Order By: Relevance
“…Compared to 1999, the number of deaths listing non-AIDSrelated causes increased more in the group that listed HIV/AIDS on the death certificate when compared to the group not listing HIV/AIDS. Other authors have reported similar results for some time in developed countries 11,12,13,14,15 .…”
Section: Discussionsupporting
confidence: 69%
“…Compared to 1999, the number of deaths listing non-AIDSrelated causes increased more in the group that listed HIV/AIDS on the death certificate when compared to the group not listing HIV/AIDS. Other authors have reported similar results for some time in developed countries 11,12,13,14,15 .…”
Section: Discussionsupporting
confidence: 69%
“…Other variables that negatively influence HCV progression have been shown to be alcohol, increasing age at acquisition and the presence of HBV infection [170][171][172][173][174][175][176][177][178].…”
Section: The Influence Of Hiv On Hcv Infectionmentioning
confidence: 99%
“…HIV-associated lung complications are also frequent causes of illness and death in industrialized nations, where the greatly improved prognosis of HIV-infected patients due to more widespread availability and access to combination antiretroviral therapy (ART) has turned HIV infection into a chronic disease. Among persons on ART, growing numbers are surviving longer and are developing comorbid diseases that significantly affect mortality, with serious ''non-AIDS'' conditions accounting proportionally for the majority of deaths in recent studies (2)(3)(4)(5)(6). This paper reviews the current state of knowledge regarding the impact of HIV on lung health, highlights ongoing research in this field, and serves as an introduction to the subsequent articles in this issue of the Proceedings of the American Thoracic Society that are each devoted to specific pulmonary and critical care complications of HIV infection.…”
mentioning
confidence: 99%